2011
DOI: 10.1007/s12011-011-8997-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Iodine Intake and Thyroid Function in Subjects with Normal Thyroid Function

Abstract: Excessive iodine intake is known to induce hypothyroidism in people who have underlying thyroid disorders. However, few studies have been performed on subjects with normal thyroid function without a history of autoimmune thyroid disease. We hypothesized that high iodine intake may cause a subtle change in thyroid function even in subjects with normal thyroid function. We analyzed 337 subjects (64 men and 273 women; mean age, 49 years) who showed normal levels of thyroid peroxidase antibodies (TPO-Ab) and thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
(25 reference statements)
0
16
1
2
Order By: Relevance
“…In their study of thyroid antibody negative Japanese pregnant women (gestational age 7-15 weeks), Orito et al found that median urinary iodine excretion during the first trimester was extremely high (328 μg/L), TSH values were positively correlated with urinary iodine, and that 1.2% of the study population had a serum TSH > 4.90 mIU/L while still having a normal FT4 [18]. It is worth noting that adult Koreans consume a diet rich in iodine [19][20][21], but it is not known what effect (if any) this would have on the reference intervals established in the present study. Ultimately, the variation of data across published reports underscores the importance of using method-and population-specific reference intervals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their study of thyroid antibody negative Japanese pregnant women (gestational age 7-15 weeks), Orito et al found that median urinary iodine excretion during the first trimester was extremely high (328 μg/L), TSH values were positively correlated with urinary iodine, and that 1.2% of the study population had a serum TSH > 4.90 mIU/L while still having a normal FT4 [18]. It is worth noting that adult Koreans consume a diet rich in iodine [19][20][21], but it is not known what effect (if any) this would have on the reference intervals established in the present study. Ultimately, the variation of data across published reports underscores the importance of using method-and population-specific reference intervals.…”
Section: Discussionmentioning
confidence: 98%
“…Iodine nutrition status was not assessed in this study as it has been previously reported that the adult Korean population consumes a diet rich in iodine (including seaweed and salt-water fish), and may in fact consume excessive iodine [19][20][21]. Due to the difficulty in obtaining agematched longitudinal samples for non-pregnant women (MizMedi is a maternal health specialty hospital), reference intervals and thyroid autoantibody status were not assessed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies regarding excess iodine suggested that high iodine intake was associated with increased incidence of hypothyroidism [19,20], while others found that it led to hyperthyroidism [21,22]. These different results may be related to the duration of high iodine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects of excess iodine were not apparent. In a study of 337 healthy South Korean adults, UI excretion had a weakly negative correlation with free T4 and showed a positive trend with TSH, whereas their levels of free T4 and TSH were within the normal ranges48). Iodine excess did not directly influence the risk of goiter in 69 Korean prepubertal children49).…”
Section: Iodine Related Health Problem In Korean Peninsulamentioning
confidence: 90%